Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Bengkel Honda Sei Rampah - Minarti, Nining; Manik, Sri Winda Hardiyanti; Pardede, Imelda Marthauli (Economic Development Progress, 2023)
The purpose of this study was to find out how work motivation influences the performance of Honda Workshop employees and to find out how work motivation influences the performance of Honda Workshop employees with job satisfaction as an intervening variable. The population in this study were Sei Rampah Honda Workshop employees who used the census method. Because the total population was less than 100, the sample in this study was 45 people. Data collection techniques using literature and questionnaires. The method used is multiple linear regression and path analysis with the help of SPSS 17.00 software. The results showed that the first hypothesis was accepted, meaning that the Work Motivation Variable (X) had a significant effect on the Job Satisfaction variable (Z). The second hypothesis is accepted, meaning that the Work Motivation Variable (X) has a significant effect on employee performance variables (Y). The third hypothesis is accepted, meaning that the job satisfaction variable (Z) has a significant effect on employee performance variable (Y).